Polynomial chaos methods for hyperbolic partial differential equations : numerical techniques for fluid dynamics problems in the presence of uncertainties /: numerical techniques for fluid dynamics problems in the presence of uncertainties. (2015) - Pettersson, Mass Per; Iaccarino, Gianluca; Nordström, Jan, 1953-
No abstract available